2014
DOI: 10.1111/hpb.12300
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of patients with stage I and II hepatocellular carcinoma after a liver transplantation or liver resection

Abstract: Liver transplantation offers a survival advantage compared with a liver resection among patients with Stage I and II HCC. LT is the best surgical treatment for early stage (I/II) HCC in patients with advanced fibrosis or cirrhosis, whereas LR provides equivalent outcomes to LT in patients without advanced fibrosis and should be considered as the first surgical option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…As expected, prognosis overall of patients with this stage disease who are treated with more aggressive therapies is good. Transplanted patients had the best survival, and survival for patients following resection, was consistent with prior work [23][24][25][26]. On adjusted analysis, we found that resected and transplanted patients' risk of death at 5 years was more than 50% and 70% decreased when compared to non-surgical therapies, respectively.…”
Section: Treatment Modality and Survivalsupporting
confidence: 88%
“…As expected, prognosis overall of patients with this stage disease who are treated with more aggressive therapies is good. Transplanted patients had the best survival, and survival for patients following resection, was consistent with prior work [23][24][25][26]. On adjusted analysis, we found that resected and transplanted patients' risk of death at 5 years was more than 50% and 70% decreased when compared to non-surgical therapies, respectively.…”
Section: Treatment Modality and Survivalsupporting
confidence: 88%
“…In mutual agreement, all publications demonstrate superiority for liver transplantation for the treatment of HCC at the early BCLC stage A [136][137][138] or AJCC stage Ⅰ and Ⅱ HCC [139] . In contrast, liver resection has been demonstrated to yield similar outcome results compared to liver transplantation in patients with incomplete cirrhosis (Ishak score 0-4), thus for these patients, liver transplantation should be avoided in this subgroup of patients [139] . Unfortunately, there are nor studies comparing liver resection and liver transplantation for patients with Child B or Child C cirrhosis.…”
Section: Transplantation Vs Liver Resectionsupporting
confidence: 52%
“…LT has been shown in multiple retrospective studies and a meta-analysis to have superior long term, recurrence-free survival compared to HR. [1014] However, the scarcity of donor livers is a limiting factor to transplantation in patients who meet criteria. Prolonged waiting times may lead to tumor progression and/or death from liver failure, and the estimated monthly drop-out rate increases with length of time on the waitlist, reaching 5.6% at 12 months.…”
Section: Discussionmentioning
confidence: 99%